Fatigue behavior of multilayer ceramic structures in traditional and reverse layering designs - Contreras, Lisseth Patricia Claudio [UNESP] (2023)
Purpose: This study evaluated the fatigue failure load (FFL) and the number of cycles for fatigue failure (CFF) of traditional (porcelain layer up) and reversed (zirconia layer up) designs of porcelain-veneered zirconia samples prepared with heat-pressing or file-splitting techniques. Materials and Methods: Zirconia discs were prepared and veneered with heat-pressed or machined feldspathic ceramic. The bilayer discs were bonded onto a dentin-analog according to the bilayer technique and sample design: traditional heat-pressing (T-HP), reversed heat-pressing (R-HP), traditional file-splitting with fusion ceramic (T-FC), reversed file-splitting with fusion ceramic R-FC), traditional file-splitting with resin cement (T-RC), and reversed file-splitting with resin cement (R-RC). The fatigue tests were performed using the stepwise approach at 20 Hz, 10,000 cycles/step, step-size of 200 N starting at 600 N, and proceeding until failure detection or up to 2600 N if enduring. The failure modes (from radial and/or cone cracks) were analyzed in a stereomicroscope. Results: The reversed design decreased the FFL and CFF of bilayers prepared with heat-pressing and file-splitting with fusion ceramic. The T-HP and T-FC reached the highest results, which were statistically similar between them. The bilayers prepared by the file-splitting with resin cement (T-RC and R-RC) were similar to the R-FC and R-HP groups regarding FFL and CFF. Almost all reverse layering samples failed by radial cracks. Conclusions: The reverse layering design did not improve the fatigue behavior of porcelain veneered zirconia samples. The three bilayer techniques behaved similarly when used in the reversed design.